Intravenous Iron Repletion Does Not Significantly Decrease Platelet Counts in CKD Patients with Iron Deficiency Anemia - Neville R. Dossabhoy; Rebecca Gascoyne; Steven Turley (International Journal of Nephrology)
Purpose. We sought to investigate the effect of IV iron repletion on platelet (PLT) counts in CKD patients with iron deficiency anemia (IDA). Methods. We conducted a retrospective chart review, including all patients with CKD and IDA who were treated with iron dextran total dose infusion (TDI) between 2002 and 2007. Patient demographics were noted, and laboratory values for creatinine, hemoglobin (Hgb), iron stores and PLT were recorded pre- and post-dose. Results. 153 patients received a total of 251 doses of TDI (mean ± SD = 971 ± 175 mg); age years and Creatinine  mg/dL. All CKD stages were represented (stage 4 commonest). Hgb and Fe stores improved post-TDI (). There was a very mild decrease in PLT (pre-TDI 255 versus post-TDI 244, ). The mild reduction in PLT after TDI remained non-significant () when data was stratified by molecular weight (MW) of iron dextran used (low versus high), as well as by dose administered (<1000 versus ≥1000 mg). Linear regression analysis between pre-dose PLT and Tsat and Fe showed R2 of 0.01 and 0.04, respectively. Conclusion. Correction of iron deficiency did not significantly lower PLT in CKD patients, regardless of MW or dose used. Correlation of PLT to severity of iron deficiency was very weak.